(untitled) (Shiksha Shastra Saurabh, 2022)
A number of factors may affect the practice of teaching and learning English language. Amid them, the motivation of, and engagement in learning can have significant impact on learning achievement in English, however, a qualitative study is required to examine the role of motivation and engagement in reading particular content. In this regard, this study aimed to explore the issues related to a reading intervention with a growing concern about English language learners’ reading achievement focusing upon learners’ participation in learning activities. Based on the data from the interviews with instructors and a focus group of students, this study revealed a significant impact of motivation of and engagement on reading activities. High-interest, yet challenging reading materials, an interactive and collaborative learning environment, and the quality of instruction and attitudes proved to be critical for students’ engagement in reading. Furthermore, English language learners faced challenges in oral reading and participation in making predictions.